DAMPAK PENGGUNAAN QUIZIZZ SEBAGAI MEDIA PEMAHAMAN PENDIDIKAN KEWARGANEGARAAN SISWA - Rahayu, Bening Mujianti; Pahamzah, Jhon; Muhyidin, Asep (Universitas Hamzanwadi, 2024)
The purpose of this study was to determine the impact of using Quizizz in the teaching and learning system at Teknologi Informatika YPML Vocational School. The research method used in this study is quantitative research with a quasi-experimental research design. The research sample consisted of 20 students from Teknologi Informatika YPML Vocational School. Data were collected through pretest and posttest. The research instruments were analyzed using validity and reliability tests. Normality test, homogeneity test and Wilcoxon signed rank test were used for data analysis. The hypothesis test results showed that Ha was accepted and Ho was rejected. The results showed that the use of Quizizz platform significantly affected the reading performance of grade 11 students at Teknologi Informatika YPML Vocational School.